Riboflavin-Responsive Multiple Acyl-CoA Dehydrogenase Deficiency Associated with Hepatoencephalomyopathy and White Matter Signal Abnormalities on Brain MRI - Vieira, Päivi; Myllynen, Päivi; Perhomaa, Marja; Tuominen, Hannu; Keski-Filppula, Riikka; Rytky, Seppo; Risteli, Leila; Uusimaa, Johanna (Neuropediatrics, 2017)
Multiple acyl-CoA dehydrogenase deficiency (MADD) is a rare inborn error of metabolism affecting both fatty acid and amino acid oxidation. It can manifest at any age, but riboflavin-responsiveness has mainly been described in less severely affected patients. We describe an infant with severe MADD presenting with profound hypotonia and hepatomegaly. Treatment with riboflavin improved his muscle strength, liver size, and biochemical markers. A homozygous mutation of electron transfer flavoprotein dehydrogenase (ETFDH) was found. His motor skills continued to progress until a fatal infection-triggered deterioration at the age of 34 months. We show changes in brain magnetic resonance imaging over the course of the disease, with profound white matter abnormalities during the deterioration phase. Aggregates of mitochondria with abnormal cristae in muscle electron microscopy were noticed already in infancy. An unusual lactate dehydrogenase (LDH) isoenzyme pattern with LDH-1 predominance was additionally observed. This case demonstrates riboflavin-responsiveness in a severely affected infant with both muscular and extramuscular involvement and further underlines the variable nature of this disease.
Keywords: MADD; glutaric aciduria type 2; ETFDH; infant